HER2-targeted advanced metastatic gastric/gastroesophageal junction adenocarcinoma: treatment landscape and future perspectives - Weiling Li; Xiaoling Zhang; Yunyi Du; Ying Zhang; Jing Lu; Wenqing Hu; Jun Zhao (BMC, 2022)
Abstract Recently, the global incidence of gastric/gastroesophageal junction (G/GEJ) cancer has remained high. China is also a large country with a high gastric cancer (GC) incidence rate, where the cases of GC account for 40% of all cases worldwide. More than 90% of GEJ cancers are the adenocarcinoma pathological type. Patients with early-stage G/GEJ adenocarcinoma may have a better prognosis after surgery. In contrast, patients with advanced metastatic G/GEJ adenocarcinoma usually choose comprehensive treatment based on systemic pharmacotherapy, but the subsequent long-term survival is not optimistic. The discovery of various biomarkers, especially microsatellite instability (MSI), programmed cell death-ligand 1 (PD-L1), human epidermal growth factor receptor 2 (HER2), tumor mutational burden (TMB) and Epstein-Barr virus (EBV), has led to the identification of an increasing number of targeted populations and has greatly improved the clinical efficacy of treatments for G/GEJ adenocarcinoma. The ToGA trial added trastuzumab to standard chemotherapy, showed improved survival of patients with HER2-positive advanced G/GEJ adenocarcinoma and brought these patients into a new era of HER2-targeted therapy. Moreover, many HER2-targeted agents have been developed and studied in patients with advanced HER2-positive G/GEJ adenocarcinoma who have demonstrated excellent clinical outcomes. However, many patients experience disease progression with HER2-targeted therapy; hence, new anti-HER2 drugs keep being developed, significantly reducing HER2 resistance. This paper reviews HER2-targeted drugs for advanced metastatic G/GEJ adenocarcinoma, potential resistance mechanisms and future directions.